THE EFFECT OF THE MEA MODEL AND LEARNING MOTIVATION ON STUDENT LEARNING OUTCOMES PPKN SUBJECTS AT SD - Eka Resti Barus; Deny Setiawan; Daulat Saragi (SENSEI RESEARCH CENTER, 2021)
This study aims to determine: 1) The effect of the AEC learning model and the expository learning model on student learning outcomes, 2) The effect of learning motivation skills on student learning outcomes. 3) The interaction between learning models and learning motivation on student learning outcomes. This study used a quasi-experimental research method. The research was conducted from April to May 2021. The population of this study was 40-grade students of SDN 034799 DOLOKTOLONG and 40 students of LANCANG SDN who were randomly assigned by random sampling technique. The sample is class IVA as many as 20 students as the experimental class and class IVB as many as 20 students as the control class. The data collection technique used a learning motivation questionnaire and a learning outcome test. The data analysis technique used two-way analysis of variance. The results of the study are as follows: (1) There are differences in learning outcomes students who were taught with the MEA learning model with an average value of 88.00 higher than the learning outcomes of students taught by the expository learning model with an average of 76,841, the analysis of variance results show Fcount value of 21.192> Ftable value of 3.24 and a probability or significance value of 0.00 <0.05 so that H0 is rejected; (2) There is a significant difference between student learning outcomes with high learning motivation and the average 88,113 and students who have low learning motivation on average 71,071. Result of analysis of variance obtained Fcount value of 7.211> Ftable value of 3.24 and a significant value of 0.00 <0.05 so that H0 is rejected; (3) There is an interaction between the AEC learning model and student motivation in improving student PPKn learning outcomes, the results of the analysis of variance Fcount value of 4.446> Ftable value of 3.24 and a significance of 0.008 <0.05 so that H0 is rejected.